The Timely Computing Base - Veríssimo, Paulo (1999)
Real-time behavior is materialized by timeliness specifications, which in essence call for synchronous system models. However, systems many often rely on large-scale, unpredictable and unreliable infrastructures, that suggest the use of asynchronous models. Several models in between have addressed these antagonistic aims, each in its own way. We propose an architectural construct that addresses the problem in a generic way. We assume the existence of a component that is capable of executing timely functions, however asynchronous the rest of the system may be. This component can be used by other components to execute timely services. There is a certain analogy to the trusted computing base principle used in security. We call it the Timely Computing Base, TCB. In this paper, we show that a TCB can be used to build dependable and timely applications exhibiting varying degrees of timing fault tolerance, under several synchrony models